1999
DOI: 10.1021/bi982848u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Restriction Endonuclease Cleavage by Triple Helix Formation with RNA and 2‘-O-Methyl RNA Oligonucleotides Containing 8-Oxo-adenosine in Place of Cytidine

Abstract: The ability of homopyrimidine oligoribonucleotides (RNA) and oligo-2'-O-methyl-ribonucleotides (2'-O-methyl RNA) containing 8-oxo-adenosine (AOH) and 8-oxo-2'-O-methyl (AmOH) adenosine to form stable, triple-helical structures with sequences containing the recognition site for the class II-S restriction enzyme, Ksp632-I, was studied as a function of pH. The AOH- and AmOH-substituted RNA and 2'-O-methyl RNA oligonucleotides were shown to bind within the physiological pH range in a pH-independent fashion, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…2 0 -O-methyl oligoribonucleotides (ORNs) are gaining widespread attention because of their newly discovered, diverse biomedical applications in viral and cancer therapies (Wan et al, 1998;Ushijima et al, 1999). RNA hybridized to 2 0 -O-methyl ORNs and incubated in nuclear extracts from HeLa cells was truncated by the inhibition of an exonuclease degrading RNA in the 3 0 to 5 0 direction (Dominski et al, 1996).…”
Section: Are-mediated Stabilization Of Mrnamentioning
confidence: 99%
“…2 0 -O-methyl oligoribonucleotides (ORNs) are gaining widespread attention because of their newly discovered, diverse biomedical applications in viral and cancer therapies (Wan et al, 1998;Ushijima et al, 1999). RNA hybridized to 2 0 -O-methyl ORNs and incubated in nuclear extracts from HeLa cells was truncated by the inhibition of an exonuclease degrading RNA in the 3 0 to 5 0 direction (Dominski et al, 1996).…”
Section: Are-mediated Stabilization Of Mrnamentioning
confidence: 99%
“…The TFOs that consisted of deoxyribonucleotides, 1d , 2d , and 3d , formed relatively stable triplexes whose third strands dissociated at approximately 50°C, a temperature lower than the melting temperature of duplex 4RY , 65°C. We and others have shown previously that incorporation of 2′- O -methylribonucleotides can stabilize TFO binding (40-45). In accord with these findings, the TFOs containing 2′- O -methylribonucleotides, 2mr and 3mr , formed triplexes that melted with a single transition at greater than 70°C.…”
Section: Resultsmentioning
confidence: 93%
“…[52] The properties of the novel oligonucleotides were tested in the inhibition of the sequence specific cleavage of simianv irus 40 DNA by endonuclease Ksp632-I. [52] The properties of the novel oligonucleotides were tested in the inhibition of the sequence specific cleavage of simianv irus 40 DNA by endonuclease Ksp632-I.…”
Section: -Oxoa In Rnamentioning
confidence: 99%
“…Ushijima et al then reported on the incorporation of 8-oxoA into oligonucleotides of RNA (using the canonical 3'-5'-linkage). [52] The properties of the novel oligonucleotides were tested in the inhibition of the sequence specific cleavage of simianv irus 40 DNA by endonuclease Ksp632-I. Between 1-3 modifications were incorporated to observe decreased T m valuesw ith increasing number of 8-oxoA units present within the formed triple-helix structures.P ossibilities for base pairing interactions with G, C, and Twere proposed as aconformational change between anti!syn is possible, with the syn conformationb eing the preferred form.…”
Section: -Oxoa In Rnamentioning
confidence: 99%